STRATEGI ISTRI PEJUDI MEMPERTAHANKAN KEUTUHAN KELUARGA DI NAGARI INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - NENGSIH, CICI WAHYU (Pendidikan Sosiologi, 2014)
This thesis examines the gamblers wife strategy in maintaining the family unit in Nagari Inderapura District of beheading Problem South Coastal District. Husband should be the backbone of the family and the responsibility of being the breadwinner is not performing its role even abandoning his wife and children because they are more of a gamble than earning a living for his wife and children that resulted in his wife who changed his position as breadwinner and meet the needs of everyday life. Nevertheless, the gamblers wife still maintain the integrity of the family. The purpose of this study was to describe the gamblers wife in maintaining the family unit in Nagari Inderapura District of beheading Problem South Coastal District. The approach used in this study is a qualitative approach, with descriptive research type. The informants are individuals that wives whose husbands gamble. Selection of informants in this study using purposive sampling technique with a number of informants 10 people. Data used primary and secondary. Data collection methods used were observation, interviews, documentation. The unit of analysis is the individual. Data analysis was performed in this study using the interactive developed by Miles and Heburman. Used for the analysis of rational choice theory proposed by James S. Coleman.The results of this study indicate that the various strategies undertaken gamblers wife in maintaining the integrity of the family such as: 1) leave their children to the grandmother / parents, this is done gamblers wife because she does not want her son to live with him when the hard life 2) Implement double living patterns, pattern double living gamblers wife as the husbands income did not meet the needs of household wife so gamblers do extra effort 3) Involve family members to meet the needs, empower all family members gamblers wife did was to survive where other than working wives their children too go to work to help the needs of the tanga 4) Reduce spending in the household, this is my wife so gamblers do not soaring household needs 5) Building partnership with local communities, it aims to facilitate the desired any gamblers wife.